2023
DOI: 10.5829/ije.2023.36.07a.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Different Sources of Alumina Silicate on Mechanical Properties and Carbonation Depth of Environmentally Friendly Geopolymeric Composite Based on Metakaolin

Abstract: Today, concrete is the most widely used building material. Cement production releases about 7% of carbon dioxide gas into the atmosphere and increases greenhouse gases, so it seems necessary to use an alternative to Portland cement. In recent years, geopolymers (mineral polymers) have been proposed as a new environmentally friendly cement. Metakaolin, bentonite, zeolite, iron blast furnace slag and fly ash can be mentioned as aluminosilicate sources. In the field of geopolymer concrete construction, few articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…*Corresponding Author Email: hussein.shaker@qu.edu.iq (H. Raad Shaker) Ordinary Portland Cement (OPC) plays a vital function in the production of concrete and the manufacturing of cement involves burning of huge quantities of fuel and breakdown of limestone, which results in large emission of carbon dioxide to the atmosphere (2). The production of one ton of Portland cement causes the release of approximately one ton of carbon dioxide into the environment and the consumption of 1.5 tons of raw materials in manufacturing one ton of cement (3). Another essential reason pushed the engineers to look for another construction material which is a catastrophic fires occurs in France in 1973, which led Davidovits to think in another non-flammable and non-combustible material (4).…”
Section: Introductionmentioning
confidence: 99%
“…*Corresponding Author Email: hussein.shaker@qu.edu.iq (H. Raad Shaker) Ordinary Portland Cement (OPC) plays a vital function in the production of concrete and the manufacturing of cement involves burning of huge quantities of fuel and breakdown of limestone, which results in large emission of carbon dioxide to the atmosphere (2). The production of one ton of Portland cement causes the release of approximately one ton of carbon dioxide into the environment and the consumption of 1.5 tons of raw materials in manufacturing one ton of cement (3). Another essential reason pushed the engineers to look for another construction material which is a catastrophic fires occurs in France in 1973, which led Davidovits to think in another non-flammable and non-combustible material (4).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a brief literature review, it has been found that multicomponent concrete with several additives has emerged as a new generation of concrete that is able to maintain the required properties in all operating conditions. The use of multicomponent concretes is growing due to their ability to manage structure formation and show directed quality in properties at all stages of technology (27,28). For example, Balamuralikrishnan et al (29) analyzed the flexural, shear, and combined effects of the flexural and shear behavior of reinforced concrete beams that were strengthened with externally bonded ferrocement laminates made with spent catalysts.…”
Section: Introductionmentioning
confidence: 99%